2021
DOI: 10.1002/term.3176
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol benefits the lineage commitment of bone marrow mesenchymal stem cells into osteoblasts via miR‐320c by targeting Runx2

Abstract: Bone marrow mesenchymal stem cells (BMSCs) are a potential source of osteoblasts and have been widely used in clinical therapies due to their pluripotency. Recent publications have found that resveratrol (RSVL) played a crucial role in the proliferation and differentiation of BMSCs; however, the underlying molecular mechanism of RSVL‐induced BMSCs osteogenic differentiation needs to be fully elucidated. The objective of this study was to explore functions of miRNAs in the RSVL‐treated BMSCs and its effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Other studies have reported that RSV induces osteoblastic differentiation in pathological and non-pathological conditions [ 47 , 48 , 49 ]. The treatment with RSV in multiple myeloma cells inhibits the growth of tumor cells and also acts on the microenvironment, inhibiting osteoclastogenesis and, thus, bone resorption and inducing osteoblastic differentiation [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that RSV induces osteoblastic differentiation in pathological and non-pathological conditions [ 47 , 48 , 49 ]. The treatment with RSV in multiple myeloma cells inhibits the growth of tumor cells and also acts on the microenvironment, inhibiting osteoclastogenesis and, thus, bone resorption and inducing osteoblastic differentiation [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression miR-320c suppressed osteoblastic differentiation of BMSCs by targeting Runx2 in RSVL, while down-regulation of miR-320c accelerated osteoblastic differentiation of BMSCs. In conclusion, miR-320c can be used as a new target to regulate the biological function of BMSCs with RSVL (25).…”
Section: Mirna Regulates Osteogenic Differentiation By Targeting Osteogenic Genesmentioning
confidence: 95%
“…After adhesion and proliferation comes the differentiation of cells. MSCs are multiprogenitor cells that can be differentiated into the desired lineage of cells under conditions that stimulate the transition [144,145]. In the case of BTE, these progenitor cells are being used to treat bone defects by differentiating them into osteoblasts and affiliated cells that will aid in the regeneration process.…”
Section: Cell Differentiationmentioning
confidence: 99%